Cooling technologies and long-term efficiency improvement of horticulture market agents: Panel data evidence from solar-powered cold-storage intervention in Nigeria - Takeshima, Hiroyuki; Yamauchi, Futoshi; Dauda, Bawa; Balana, Bedru (International Food Policy Research Institute, 2024)
Modern cooling technologies, including cold storage, have been considered one of the critical tools to address increasingly complex challenges in agrifood systems in developing countries, including poverty, economic growth, food loss and waste, food and nutrition security, and environmental sustainability (e.g., IFPRI 2020; Kashyap & Agarwal 2020). Cold storage can minimize most human pathogens, ensuring enhanced food safety (Uçar & Özçelik 2013; Kopp & Mishra 2022) and contribute to increased consumption of micronutrient-rich horticulture crops (Schreinemachers et al. 2018). Cooling technologies can also improve market functions by enabling higher and more stable prices received by suppliers (Rakshit 2011; Schreinemachers et al. 2018) and reducing losses (Allen & de Brauw 2018). Cooling-chain development has been a significant part of food system transformation outside Africa South of the Sahara (SSA) (IFPRI 2020). Similar technologies may become more broadly relevant in SSA in the near future (Tschirley et al. 2015). Traditionally, the use of cold storage has been constrained by high energy consumption and adverse environmental effects like carbon emissions (Pueyo et al. 2020; Steyn et al. 2016). However, a growing set of potential energy solutions are being proposed and introduced on a pilot basis, including solar power (Takeshima et al. 2023).